Reproductive phenology of yellow pitaya in a high-altitude tropical region in Brazil - Josimara Mendes Rabelo; Maria do Céu Monteiro Cruz; Deilson de Almeida Alves; João Esdras Lima; Letícia Alves Carvalho Reis; Nubia Cassiana Santos (Acta Scientiarum: Agronomy, 2020)
Pitaya species cultivation in Brazil is recent, and information on the production of the species Selenicereus megalanthus, known as yellow pitaya, is non-existent because research in the country has focused on the species Hylocereus undatus. The research was carried out with the objective of evaluating the reproductive phenology of the species S. megalanthus, in a high-altitude climate conditions in Brazil. The study orchard of yellow pitaya was located at an altitude of 726 metres, 18º 04' 15" S latitude and 43º 28' 15" W longitude, and has an Aw climate, classified as high-altitude tropical. Phenological evaluations were carried out through visual observations, from the beginning of floral button formation until the end of the fruit harvest, during three production cycles. On each plant, flower buds were marked to determine the time from floral button formation until flower anthesis and from flower fertilisation until fruit ripening. The period of flowering and harvesting of the yellow pitaya was determined according to the phenological stage records. Flowering began in the spring, with successive flowering events until the autumn. The time between floral button formation until anthesis ranged from 46 to 55 days. The time from flower fertilisation until fruit ripening ranged from 96 to 110 days. Fruit harvest began in the summer and ended in winter. The reproductive cycle of S. megalanthus is longer than H. undatus and H. polyrhizus, which are also cultivated in Brazil, ranging from 147 to 166 days from floral button formation to fruit harvest.